Examining the Drivers of Human Development in European Union - Maria-Daniela Tudorache (Proceedings of 35th IBIMA Conference, Seville, Spain, 2020)
This paper provides an analysis of the human development drivers in the European Union. The variables used cover the 2010-2017 period, during which the Member States have faced different economic and social challenges generated by the global economic crisis. In the analysis, I used Panel Estimated Generalized Least Squares, weighted with the Period SUR option. The paper confirms a direct relationship between three independent variables (life expectancy, corruption perception index and gross fixed capital formation) and the dependent variable - the human development index. In this context, the study demonstrated that a decrease in the dimension of corruption leads to an increase in the human development, since the growth of corruption perception index is associated with a fall in the corruption dimension. On the other hand, an inverse relationship was identified between the other two exogenous variables (the share of people leaving education and training early, respectively employment in agriculture) and the human development index.
Keywords: O15; D73; I25; J21; 330; human development; corruption; employment; education